2005
DOI: 10.1159/000083366
|View full text |Cite
|
Sign up to set email alerts
|

Normative Findings of Electrically Evoked Compound Action Potential Measurements Using the Neural Response Telemetry of the Nucleus CI24M Cochlear Implant System

Abstract: One hundred and forty-seven adult recipients of the Nucleus 24 cochlear implant system, from 13 different European countries, were tested using neural response telemetry to measure the electrically evoked compound action potential (ECAP), according to a standardised postoperative measurement procedure. Recordings were obtained in 96% of these subjects with this standardised procedure. The group results are presented in terms of peak amplitude and latency, slope of the amplitude growth function and ECAP thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
55
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 29 publications
10
55
1
2
Order By: Relevance
“…Since electrodes 14 and 19 did not cause FNS at C level, but led to some hearing sensations, these electrodes were switched on. Multicenter NRT data reported that ECAPs could be elicited in 96% of the cases [Cafarelli et al, 2005]. It is obvious that this is not found in the OI patients.…”
Section: Spatial Spread Of Neural Excitationmentioning
confidence: 94%
“…Since electrodes 14 and 19 did not cause FNS at C level, but led to some hearing sensations, these electrodes were switched on. Multicenter NRT data reported that ECAPs could be elicited in 96% of the cases [Cafarelli et al, 2005]. It is obvious that this is not found in the OI patients.…”
Section: Spatial Spread Of Neural Excitationmentioning
confidence: 94%
“…Previous studies have demonstrated that there is a certain level of conformity in the M-and T-level profiles, both of which tend to increase toward the basal end of the cochlea [Smoorenburg, 2007]. This increase has been observed for cochlear implants produced by different manufacturers (Cochlear Corp., Lane Cove, Australia; Advanced Bionics, Sylmar, Calif., USA; MedEl Corp., Innsbruck, Austria) [Baudhuin et al, 2012;Botros and Psarros, 2010;Cafarelli et al, 2005;D'Elia et al, 2012;Lai et al, 2009;Miller et al, 2008;Polak et al, 2005;Smoorenburg et al, 2002;Thai-Van et al, 2001;van der Beek et al, 2015;Vargas et al, 2013]. Furthermore, both perimodiolar and more lateral electrodes (Nucleus Straight vs. Contour) show higher levels basally [Polak et al, 2004].…”
Section: Introductionmentioning
confidence: 91%
“…The general conclusion of these studies is that objective measures can be indicative of levels, but unfortunately, significant correlations between eSRT, eABR and eCAP measurements and T-and M-levels were shown to be of moderate strength and not appropriate for predictions in individual users. Some studies found a substantial correlation of the level profile with the eCAP profile (r = 0.82) [Smoorenburg et al, 2002], but this could not be confirmed by others [Cafarelli et al, 2005;Abbas et al, 2006]. The eCAP thresholds are routinely above behavioral thresholds but not always below maximum comfort levels [Miller et al, 2008].…”
mentioning
confidence: 93%
“…In an attempt to produce a reasonably automated prediction of levels and facilitate the fitting process, many studies have investigated whether objective measures such as evoked stapedius reflex threshold (eSRT), auditory brain stem response (eABR) or compound action potential (eCAP) could predict the T-and M-levels or level profiles [Shallop et al, 1991;Mason et al, 1993;Brown et al, 1994Brown et al, , 1999Hodges et al, 1999;Brown et al, 2000;Allum et al, 2002;Seyle and Brown, 2002;Smoorenburg et al, 2002;Brown, 2003;Gordon et al, 2004;Cafarelli et al, 2005;Caner et al, 2007;Miller et al, 2008;Alvarez et al, 2010;Botros and Psarros, 2010;Jeon et al, 2010]. The general conclusion of these studies is that objective measures can be indicative of levels, but unfortunately, significant correlations between eSRT, eABR and eCAP measurements and T-and M-levels were shown to be of moderate strength and not appropriate for predictions in individual users.…”
mentioning
confidence: 99%